STUDY OF THE OVARIANS ACTIVITIES OF THE LOCAL GOAT IN DIFFERENT SEASONS OF YEAR IN DOHUK PROVINCE - Muoffig S. Barwary (Mesopotamia Journal of Agriculture)
The study was conducted in the Dept. of Animal Production College of Agriculture, University Duhok . 230 local goat ovarian samples were tested . These samples were collected from the slaughter house of Duhok area. Physiological activities of these samples were determined during 3 seasons of a year. These were 91 samples (39.57%) from non pregnant goat and 139 samples (60.43%) from pregnant goats. The sexual activities of the three samples were measured then weight of ovaries and corpus lumen found in the ovaries during the three reasons. The ovarian shapes of the non pregnant goat were kidney shape and rounded while in the pregnant goat were oval and elongated , the weight and size of the right ovaries were higher than that of the left ovaries , and were different whether the animal was pregnant or not , and weight of corpora letea in the ovaries. The percent of corpora letea in the right ovary for the three stages (parturition, suckling and in semi nation) in the non pregnant ovaries were 42.8 , 38.2 and 87.5% respectively while in the pregnant animals were 94.3 , 73.8 and 86.4% in the right ovary and 43.4 , 42.2 and 18.2 in the left ovary respectively . The size of corpora letea in right ovary was bigger in size and weight than that in the left ovary . The percent of single embryo was 65.09 most of them in the right horn (84.55%) , while the percent of twin was 33.14% some of them in the right horn (37.5) and (62.5%) in the left side and one case of triple (1.77%).